The Principle of Al-Ḥudūd Tasquṭ bisy-Syubuhāt: An Analysis of the Concept, Arguments, and Implications in Contemporary Islamic Criminal Law - Amalia DT, Kiki Reski; Fauziah, Nur Aidah; Musyahid, Achmad; Kuba, Imran Anwar (al-Rasῑkh: Jurnal Hukum Islam, 2025)
The application of hudud in Islamic criminal law requires the highest level of legal certainty due to its direct relation to the protection of life, dignity, and individual freedom. The concept of shubha functions as a crucial safeguard to prevent judicial error in punishments that are fixed and irreversible. This study aims to analyze the concept, legal foundations, and contemporary implications of the maxim al-hudud tasqut bi al-shubuhat. Using a qualitative descriptive literature study, the research reveals four key findings: shubha operates as a barrier to enforcing hudud when doubt exists in the act, intention, or evidence; classical and modern scholars consistently affirm that even minimal doubt nullifies hudud to preserve justice; the judicial practice of the Prophet’s Companions demonstrates exceptional caution toward ambiguous cases; and the standard of proof for hudud must reach absolute certainty. The study concludes that shubha serves as a fundamental principle for ensuring substantive justice. Its main contribution lies in strengthening the relevance of this maxim within modern Islamic criminal law discourse.